Repercussões endodônticas dos procedimentos clareadores - Campos, Edson Alves de [UNESP]; Gonzaga, Carla Castiglia; Baratto Filho, Flares (My University, 2011)
Tooth bleaching is a treatment modality that raises great interest, due to the important role played by aesthetics in current life style. To perform such procedure, nowadays, there are several bleaching substances at several concentrations, as well as, diverse clinical techniques. When suggesting this procedure, the dentist should take into consideration several factors related to the patient to determine which will be the most appropriate technique/material combination for solving the clinical problem. The procedure indication should not only be based on the expectations exhibited by the patient, but also on respecting the biological principles to maintain the integrity of both the endodontic and periodontal tissues.

O clareamento dental é uma modalidade de tratamento que vem despertando grande interesse, sobretudo em função do importante papel assumido pela estética no estilo de vida contemporâneo. Para a realização desse procedimento existem atualmente diferentes substâncias clareadoras, que são encontradas em várias concentrações, e também diversas técnicas clínicas. Ao sugerir o clareamento, o cirurgião-dentista deve levar em consideração vários fatores relacionados ao paciente para determinar qual será a combinação de técnica/material mais adequada para a resolução do problema clínico. A indicação do procedimento não pode basear-se apenas nas expectativas apresentadas pelo paciente, mas tem de estar pautada principalmente no respeito aos princípios biológicos para a manutenção da integridade dos tecidos endodônticos e periodontais.
The endodontic consequences of tooth bleaching procedures
Keywords: Tooth bleaching; Endodontics; Resorptions; Clareamento; Endodontia; Reabsorções